2021
DOI: 10.1016/j.bioelechem.2021.107895
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical analysis of a microbial electrochemical snorkel in laboratory and constructed wetlands

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Recently, the possibility of applying the MES composed of stainless steel electrodes immersed in sediment and in water for nitrate reduction was analyzed [85]. In this study, the principle of the MES was confirmed by measuring continuously the current flowing in shortcircuit from the anodic to the cathodic sides and nitrate addition induced clearly an increase of the biocathodic activity.…”
Section: Microbial Electrochemical Snorkel (Mes)mentioning
confidence: 64%
“…Recently, the possibility of applying the MES composed of stainless steel electrodes immersed in sediment and in water for nitrate reduction was analyzed [85]. In this study, the principle of the MES was confirmed by measuring continuously the current flowing in shortcircuit from the anodic to the cathodic sides and nitrate addition induced clearly an increase of the biocathodic activity.…”
Section: Microbial Electrochemical Snorkel (Mes)mentioning
confidence: 64%
“…20 Alternatively, electro-active bacteria can use an electrode as an electron and energy source for reducing nitrate in a promising process called bioelectrochemical denitrification (or electrotrophic denitrification). 21,22 In this process, the electrode (cathode) acts as an inexhaustible electron source avoiding the need for a continuous supply of external chemical compounds for denitrification of wastewater with low availability of carbon sources. [23][24][25][26][27] Furthermore, the application of bioelectrochemical denitrification under aerobic conditions allows ammonia removal to be performed in the same reactor.…”
Section: Introductionmentioning
confidence: 99%
“…The nitrate-reducing bio-cathodes can efficiently treat nitratepolluted wastewater. 15 Conventional treatment methods require the addition of energy and organic matter. The use of autotrophic denitrification is preferred to remove nitrate from groundwater with low organic matter content and high nitrate level, which is planned to be used as a drinking water source.…”
Section: Introductionmentioning
confidence: 99%